Skysisters - Waboose, Jan Bourdeau (Kids Can Press, 2000)
Two Ojibway sisters set off across the frozen north country to see the SkySpirits' midnight dance, and after an exhilarating walk and patient waiting, the girls are rewarded by the arrival of the SkySpirits--the Northern Lights.